Toby in Charge: A Mind and Body Mystery. Issue 3 (3rd July 2019) - Pass, Stephanie
Abstract: This article discusses the treatment of a fearful and controlling 3-year-old boy who required rigid adherence to his idiosyncratic routines. The author describes her investigation into the etiology of his imperious and self-defeating behavior—reaching beyond psychodynamic models to consider early trauma and physiological aspects of his experience. Proposing an approach that draws on these perspectives, she discusses the i mplications for how we think about symptoms and about personality itself. Through close consideration of vignettes from the play therapy and the collateral sessions with his parents, she describes and explains Toby's significant and moving progress.